The Effect Of Human Resource Development On Employee Performance Moderated By Training At The South Binjai District Office - Ida Sufianty; Muhammad Isa Indrawan (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the effect of human resource development (HRD) and training on employee performance at the South Binjai District Office, and to test the role of training as a moderating variable. The study used a casual associative quantitative method with data analysis techniques using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). Data were collected through questionnaires distributed to 117 employees. The results showed that HRD development did not have a significant effect on employee performance, with a T-Statistic value of 0.249 (<1.96) and a P-Value of 0.804 (>0.05). On the other hand, training had a positive and significant effect on employee performance, with a T-Statistic value of 5.511 (>1.96) and a P-Value of 0.000 (<0.05). However, training was not able to moderate the relationship between HR development and employee performance, with a T-Statistic value of 0.636 (<1.96) and a P-Value of 0.526 (>0.05). This study confirms the importance of training as a major factor in improving employee performance, while HR development requires a more relevant and integrated approach. By strengthening training strategies and better evaluation of HR development programs, organizations are expected to significantly increase employee productivity.